Phytopathological aspects of precision agriculture - Csép, Nicolae Ioan (Acta Agraria Debreceniensis, 2012)
This paper illustrates the efforts based on the results obtained in the funding of precision agriculture, during more than two decades of cooperation between University of Debrecen and University of Oradea, within the framework of joint, EU co-financed projects, and put into practice on both sides of the border. Common plant-health databases, interactive Web pages, consultation activities, professional publications, professional training activities, laboratory infrastructure improvements, common research themes proves the progress made to date and create conditions for further development of joint research activities.